Relevance of an intelligent tutorial agent for virtual reality training systems. (1st January 2002) - Lourdeaux, Domitile; Fuchs, Philippe; Burkhardt, Jean-Marie; Bernard, Franck
Virtual reality (VR) is mostly used as a technical means of immersing the user in a computer-generated situation where the reality is the model to be perfectly recreated. Trainers often provide supportive explanations by using tutorial situations that do not exactly reproduce reality. Therefore, VR systems should also provide such tutorial situations. In order to address this issue, an intelligent tutorial agent has been designed to support the learning process. The agent is based on a cognitive taxonomy of the trainee's behaviour in the VR context. For each trainee, the agent provides two kinds of tutorial according to his/her knowledge level. The first one consists of modifying the scenario and the second one consists of guiding the trainee. These strategies can be represented by different fidelity levels of virtual environments (e.g. enhancement, simplification). They can be activated by the trainee, by the trainer or automatically. They are specified off-line and continuously modified on-line. An application of this intelligent agent is being implemented in a VR simulation-based training system for SNCF train drivers. The goal of this application is to teach the procedure to control and handle switches on high speed train tracks.